Urethral syringocele: unseen but existing. Issue 6 (5th March 2019) - Saadat, Paria; Borzi, Peter; Patel, Bhavesh; Winkle, David
Abstract : Background: Bulbourethral syringocele is an uncommon and under‐diagnosed condition most commonly seen in the paediatric population, although there is increasing recognition in adults. Due to the difficulty in diagnosis, we report our experience of urethral syringocele in a quaternary paediatric hospital, with differing presentations, diagnosis and treatment. Methods: This is a retrospective review of seven cases of children over a period of 14 years, including their presentations, diagnosis, treatment and follow‐up. A review of the current literature is presented. Results: The median age of these seven cases at presentation was 11 years (6 days to 16 years). Clinical features varied with age, with obstructive uropathy in a neonate, urinary tract infection in an infant, scrotal abscess in two children and lower urinary tract obstructive symptoms in three teenagers. Diagnostic voiding cystogram diagnosed the majority of syringoceles and two were seen on magnetic resonance imaging. Five boys underwent endoscopic transurethral deroofing and two children required transperineal marsupialization. Long‐term follow‐up showed all had complete resolution of symptoms. Conclusion: Urethral syringocele presents from the neonatal period to late adolescence, with the presenting features reflective of age. Surgical management can be performed endoscopically or by open approach. Awareness of this condition and inclusion in the differential diagnosis, particularly in the setting of an atypical or recurrent scrotal abscess, could avoid a prolonged therapeutic course. Abstract : This article summarizes our experience in urethral syringocele. It is the presentation, diagnosis and treatment to further clarify the importance of this rare diagnosis.